2006
DOI: 10.1007/s10565-006-0139-4
|View full text |Cite
|
Sign up to set email alerts
|

Protectors against doxorubicin-induced cardiotoxicity: Flavonoids

Abstract: Doxorubicin is a widely used anthracycline anticancer agent. Its use may cause cardiomyopathy: in fact, the development of cumulative dose-related cardiotoxicity forms the major limitation of clinical doxorubicin use. We therefore searched for protective agents that combine iron-chelating and oxygen radical-scavenging properties. Moreover, any novel protector should not interfere with the cytostatic activity of doxorubicin. After extensive in vitro screening we found that flavonoids could serve this purpose. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…As for many other chemotherapeutic agents, the clinical use of doxorubicin is hampered by several side effects, including cardiotoxicity (Bast et al, 2007), which is the major limitation to doxorubicin use and impairs the clinical response and the survival of patients (Bryant et al, 2007). To limit the myocardial damage, less cardiotoxic doxorubicin derivatives (Batist et al, 2001) or the coadministration with cardioprotectors, such as dexrazoxane, coenzyme Q10 (Batist et al, 2001), and flavonoids (Bast et al, 2007), has been proposed without obtaining satisfying results.…”
Section: Discussionmentioning
confidence: 99%
“…As for many other chemotherapeutic agents, the clinical use of doxorubicin is hampered by several side effects, including cardiotoxicity (Bast et al, 2007), which is the major limitation to doxorubicin use and impairs the clinical response and the survival of patients (Bryant et al, 2007). To limit the myocardial damage, less cardiotoxic doxorubicin derivatives (Batist et al, 2001) or the coadministration with cardioprotectors, such as dexrazoxane, coenzyme Q10 (Batist et al, 2001), and flavonoids (Bast et al, 2007), has been proposed without obtaining satisfying results.…”
Section: Discussionmentioning
confidence: 99%
“…One promising approach to solve this problem is the application of cochemotherapeutic agent in cancer therapy (Brenner, 2002). Co-chemotherapy may increase chemotherapeutic agents' efficacy, allowing the use of lower dosage of chemotherapeutic agent, resulting in the decrease of toxicity on normal tissues (Bastl et al, 2007). Increasing efficacy may be obtained by combining agents with established chemotherapeutic agents having additive or synergistic effect, while decreasing the toxicity may be achieved by the use of agents possessing immunomodulatory effect (Olson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids, a group of polyphenols, possess potent cardioprotective efficacy and significantly reduce the risk of cardiovascular disease (Bast et al, 2007;Du et al, 2007;Peluso, 2006;Huxley and Neil, 2003). Some research groups have reported that flavonoids exhibit protective effects against cardiomyopathy and cardiomyocyte apoptosis induced by doxorubicin (Bagchi et al, 2003;Hüsken et al, 1995).…”
Section: Introductionmentioning
confidence: 99%